The Concept of Sleep in the Stories of Victor Pelevin - Gonchar-Khanjyan, Natalie; Karapetyan, Inga (Bulletin of Yerevan University B: Philology, 2024)
The phenomenon of sleep is essential for understanding cross-cultural myth and is widely reflected in religious and philosophical teachings, historiography and fiction. The dream as a leitmotif, as the basis of the plot or the key to solving a complicated riddle appears in literature at the dawn of its emergence, is found in the works of Plato, Aristotle, and Chinese philosophers, and the dream of the Taoist sage Zhuang Ji became the prototype of a number of literary narratives. The oneiric technique of text modeling is widely used in postmodern literature, which draws endless themes and plots from the oneirosphere.The subject of this article is separate texts (stories and novels) of the early Pelevin, the cultural analysis of which allows us to supplement the extensive critical base for studying the phenomenon of the popular postmodernist writer Viktor Pelevin. The purpose of the article is, based on comparative and analytical methods, to consider separate texts of the writer in parallel with religious-philosophical (Swedenborg, Chatterjee Braman, John Donne) and psychological (Grof) concepts, to determine the main priorities and artistic models of the writer’s creativity in the context of the chosen topic.
Keywords: Pelevin; dream; reality; leading concept; post-existential hero